الحماية الجنائية للتعاملات الالكترونية في التشريع الجزائري - ضفاء خضري; عبير غريب (My University, 2021)
Abstract : Electronic transactions mean all activities that are carried out by means of modern information and communication technology, the most important of which is the Internet. Where products and services are exchanged between companies, groups and individuals, but these activities, like any other business, are subject to a group of attacks represented in the so-called electronic crimes in their traditional or modern form. Given the importance of these transactions in daily life and in the development and economic development of countries, it was necessary to provide necessary protection for them, including substantive and procedural protection as they differ from the rest of the trial procedures for ordinary crimes. ..................... Summary: Electronic transactions mean all activities carried out by modern ICTs, the most important of which is the Internet. Products and services are exchanged between companies, groups and individuals, but these activities are the same as any other business on which a range of attacks is involved, consisting of so-called cybercrime in its traditional or emerging form. Given the importance of such dealings in everyday life and in the economic development and development of States, necessary protection, including substantive and procedural protection, had to be provided as distinct from the rest of the ordinary crimes trial process. ................... ملخص : المعاملات الالكترونية يقصد بها كافة الانشطة التي تتم بواسطة تكنولوجيا المعلومات والاتصالات الحديثة اهمها شبكة الانترنت. حيث يتم تبادل المنتجات والخدمات بين الشركات والجماعات والافراد ، لكن هاته الانشطة مثلها مثل أي عمل تجاري آخر تقع عليها مجموعة من الاعتداءات تتمثل فيما يسمى بالجرائم الالكترونية بشكلها التقليدي او المستحدثة. ونظرا لأهمية هاته التعاملات في الحياة اليومية وفي التنمية والتطور الاقتصادي للدول، كان لابد من توفير حماية لازمة لها تشتمل علي الحماية الموضوعية والإجرائية كونها تختلف عن باقي إجراءات المحاكمة الخاصة بالجرائم العادية. .................. Résumé : Les transactions électroniques désignent toutes les activités menées par les TIC modernes, dont la plus importante est Internet. Les produits et services sont échangés entre les entreprises, les groupes et les individus, mais ces activités sont les mêmes que toute autre entreprise sur laquelle une gamme d’attaques est impliquée, consistant en ce que l’on appelle la cybercriminalité sous sa forme traditionnelle ou émergente. Compte tenu de l’importance de ces transactions dans la vie quotidienne et dans le développement économique et le développement des États, la protection nécessaire, y compris la protection matérielle et procédurale, devait être assurée séparément du reste du processus de procès pour crimes ordinaires.